Relationship between Abdominal Obesity and Insulin Resistance, Growth Hormone, and Insulin-like Growth Factor-1 in Individuals with Type 2 Diabetes: Relationship between abdominal obesity and biochemical factors - Lu Wen,; Cheng Chen,; Keji Zhou, (Cellular and Molecular Biology, 2022)
This experiment was designed to investigate the correlation between abdominal obesity and insulin resistance (IR), growth hormone (GH) and insulin-like growth factor-1 (IGF-1) in patients with type 2 diabetes mellitus (T2DM). To do this experiment, 200 patients with T2DM were enrolled in this cross-sectional study. They were divided into the control group (T2DM without abdominal obesity) and the observation group (T2DM combined with abdominal obesity) according to the diagnostic criteria of abdominal obesity. General data and biochemical indices were recorded from all patients. Results showed that 97 patients (48.50%, 97/200) with abdominal obesity were included in the observation group, and 103 patients (51.50%,103/200) without abdominal obesity were included in the control group. Meanwhile, the body weight, BMI, waist circumference and waist-to-hip ratio were higher in the observation group than in the control group (P<0.05). Meanwhile, the visceral fat in the observation group, TC, and TG were higher (P<0.05) compared with the control group (Visceral Fat, 92.55±3.07 vs 87.63±3.14. TC, 5.14±0.48 vs 4.97±0.51), and TG,1.89±0.13 vs 1.53±0.16). In addition, the levels of FBG, FINS and HOMA-IR were higher (P<0.05) in the observation group than those in the control group (FBG, 13.06± 2.17 vs 10.62±2.35. FINS, 16.25±2.14 vs 13.33±3.21. HOMA-IR, 9.43±1.90 vs 6.29±2.10). However, the levels of GH and IGF-1 were lower (P<0.05) in the observation group than those in the control group (GH, 1.16±0.08 vs 1.24±0.11. IGF-1, 125.14±11.46 vs 135.71±12.33). Spearman's correlation analysis showed that abdominal obesity was positively correlated with IR (R0.372, P=0.000) in patients with T2DM, while negatively correlated with GH (R=-0.271, P=0.000) and IGF-1(R-0.219, P=0.000) levels. In conclusion, abdominal obesity in patients with T2DM is positively associated with IR, and negatively correlated with GH and IGF-1 levels. Thus, improvement of IR as well as regulating the levels of growth hormone and IGF-1 might play crucial roles in the early prevention and efficient clinical treatment of T2DM with abdominal obesity patients.